Lymphangitis carcinomatosa from gallbladder cancer. (2022) - Kitahara, Yoshihiro; Taniyama, Daiki; Kuraoka, Kazuya; Saito, Akihisa; Zaitsu, Junichi; Oga, Kenichi; Senoo, Misato; Araki, Yusuke; Yamaguchi, Atsushi; Nakano, Kikuo
Abstract: A 61-year-old woman was admitted to our hospital with productive cough and fever. Computed tomography images revealed ground glass opacities in both lung fields, and a space-occupying lesion in the gallbladder. Transbronchial lung biopsy revealed a poorly differentiated adenocarcinoma with invasion of the lymph ducts; accordingly, a diagnosis of lymphangitis carcinomatosa was made. We could not administer chemotherapy due to poor performance status, and the patient died of respiratory failure 30 days after admission. Owing to pathological autopsy findings of poorly differentiated adenocarcinoma in the gallbladder, we diagnosed this as a rare case of gallbladder cancer presenting with lymphangitis carcinomatosa.